Uncovering EFL Learners’ Writing Problems and Effective Approaches to Overcome Them - Siti Lina Nurlina; Salsa Ayu Denistiani; Aldha Williyan (LEOTECH: Journal of Learning Education and Technology, 2024)
This study aims to investigate the writing difficulties experienced by EFL learners and identify possible solutions to overcome these challenges. Writing skills are considered one of the essential competencies in English learning; however, many students perceive writing assignments as challenging and complex. Although mastery of writing skills is an important indicator of successful learning, many learners still encounter difficulties in developing effective written communication, particularly in academic contexts. Students are required to acquire fundamental writing skills to support their future academic needs, including thesis and research writing. This study focuses on EFL learners from the English Department of IPB Cirebon who are enrolled in academic writing courses. The differences in students’ English proficiency levels create various challenges in the learning process, especially in generating ideas, organizing information, and applying appropriate writing structures. Therefore, understanding students’ writing difficulties is necessary to provide appropriate learning strategies and instructional approaches. This research is expected to contribute to a deeper understanding of EFL learners’ writing problems and provide insights for future studies in developing effective methods for teaching academic writing. The findings may also support educators in improving writing instruction and helping learners enhance their writing competence.